The Neutrophil: Constant Defender and First Responder - Fine, Noah; Tasevski, Nikola; McCulloch, Christopher A.; Tenenbaum, Howard C.; Glogauer, Michael (Frontiers in Immunology, 2020)
The role of polymorphonuclear neutrophils (PMNs) in biology is often recognized during pathogenesis associated with PMN hyper- or hypo-functionality in various disease states. However, in the vast majority of cases, PMNs contribute to resilience and tissue homeostasis, with continuous PMN-mediated actions required for the maintenance of health, particularly in mucosal tissues. PMNs are extraordinarily well-adapted to respond to and diminish the damaging effects of a vast repertoire of infectious agents and injurious processes that are encountered throughout life. The commensal biofilm, a symbiotic polymicrobial ecosystem that lines the mucosal surfaces, is the first line of defence against pathogenic strains that might otherwise dominate, and is therefore of critical importance for health. PMNs regularly interact with the commensal flora at the mucosal tissues in health and limit their growth without developing an overt inflammatory reaction to them. These PMNs exhibit what is called a para-inflammatory phenotype, and have reduced inflammatory output. When biofilm growth and makeup are disrupted (i.e. dysbiosis), clinical symptoms associated with acute and chronic inflammatory responses to these changes may include pain, erythema and swelling. However, in most cases, these responses indicate that the immune system is functioning properly to re-establish homeostasis and protect the status quo. Defects in this healthy everyday function occur as a result of PMN subversion by pathological microbial strains, genetic defects or crosstalk with other chronic inflammatory conditions, including cancer and rheumatic disease, and this can provide some avenues for therapeutic targeting of PMN function. In other cases, targeting PMN functions could worsen the disease state. Certain PMN-mediated responses to pathogens, for example Neutrophil Extracellular Traps (NETs), might lead to undesirable symptoms such as pain or swelling and tissue damage/fibrosis. Despite collateral damage, these PMN responses limit pathogen dissemination and more severe damage that would otherwise occur. New data suggests the existence of unique PMN subsets, commonly associated with functional diversification in response to particular inflammatory challenges. PMN-directed therapeutic approaches depend on a greater understanding of this diversity. Here we outline the current understanding of PMNs in health and disease, with an emphasis on the positive manifestations of tissue and organ-protective PMN-mediated inflammation.